Etika Komunikasi Digital dalam Public Relations dan Tantangan Profesional di Era Digital - Khatrin Is Mawardani; Ayuk Nofitasari; Kholifah Gatan Naufal; Satria Hadi Saputra; Naufal Athiya Primananda (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The rapid development of digital technology has significantly transformed the practice of public relations, particularly in the way organizations communicate with the public through digital platforms. However, the ease of information dissemination also raises ethical issues such as misinformation, privacy violations, and the spread of harmful content. This study aims to analyze digital communication ethics in public relations and identify professional challenges in the digital era. This research uses a qualitative approach with a literature study method by reviewing relevant scientific sources, including accredited national journals, international journals, and academic publications. The findings indicate that ethical principles such as transparency, accuracy, and responsibility are essential in maintaining organizational credibility and public trust. In addition, public relations professionals face challenges such as the speed of information flow, crisis communication risks, and increasing public demands for transparency. The study also reveals that there is a strong relationship between ethical communication practices and professional challenges, requiring both individual competence and organizational support. Therefore, the implementation of digital communication ethics is crucial in ensuring sustainable relationships between organizations and the public in the digital era